2016
DOI: 10.1002/2016ja022857
|View full text |Cite
|
Sign up to set email alerts
|

Solar quiet current response in the African sector due to a 2009 sudden stratospheric warming event

Abstract: We present solar quiet (Sq) variation of the horizontal (H) magnetic field intensity deduced from Magnetic Data Acquisition System (MAGDAS) records over Africa during an unusual strong and prolonged 2009 sudden stratospheric warming (SSW) event. A reduction in the SqH magnitude that enveloped the geomagnetic latitudes between 21.13°N (Fayum FYM) in Egypt and 39.51°S (Durban DRB) in South Africa was observed, while the stratospheric polar temperature was increasing and got strengthened when the stratospheric te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…Enhancement in the westward perturbation that can be expected at low to middle latitudes according to numerical simulations (Liu et al, ), should further increase this downward drift. In addition, as magnetic declination varies with longitude, SSW‐induced perturbations to the zonal wind could contribute to significant longitudinal differences in ionospheric effects reported by multiple authors (Bolaji et al, ; Goncharenko et al, ; Maute et al, ; Vieira et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement in the westward perturbation that can be expected at low to middle latitudes according to numerical simulations (Liu et al, ), should further increase this downward drift. In addition, as magnetic declination varies with longitude, SSW‐induced perturbations to the zonal wind could contribute to significant longitudinal differences in ionospheric effects reported by multiple authors (Bolaji et al, ; Goncharenko et al, ; Maute et al, ; Vieira et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal dependence of these perturbations at the low-latitude ionosphere during SSW has also been demonstrated by satellite and ground-based measurements (Bolaji et al, 2016;Fejer et al, 2010;Goncharenko et al, 2013;Jonah et al, 2014;Liu et al, 2011;Paes et al, 2014). Using the ground-based magnetometer measurements in the America, Indian, and Pacific equatorial regions during 2002-2003SSW, Fejer et al (2010 showed that morning and afternoon current perturbations are strongest in American sector and weakest (particularly in the afternoon) in the Pacific sector.…”
Section: Introductionmentioning
confidence: 88%
“…Paes et al () pointed out that the EIA suppression is stronger than its intensification in the Brazilian sector during 2008–2009 and 2009–2010 SSW events, which is opposite to the observations over the Peruvian sector. Bolaji et al () observed a reduction in the S q H (solar quite variation of the horizontal magnetic field intensity) magnitude and a reversal in the EEJ in South Africa sector during 2009 SSW, which is largest in the South American sector and smallest in the Central Asian sector.…”
Section: Introductionmentioning
confidence: 99%
“…The zonal and meridional winds in the mesospheric and lower thermospheric (MLT) region during wintertime are generally eastward and northward over the middle and low latitudes, respectively. However, the SSW can significantly affect the variations of dynamical structures in the MLT region (Chandran et al, 2013; Hoffmann et al, 2007; Ma et al, 2017; Wit et al, 2015) and even in the ionosphere (Bolaji et al, 2016; Owolabi et al, 2019; Siddiqui et al, 2015; Yamazaki et al, 2012). The neutral winds after the onset of SSW are observed to reverse to westward and southward (Chen et al, 2012; Dowdy et al, 2007; Lima et al, 2012; Sathishkumar & Sridharan, 2009; Wang & Alexander, 2009; Yuan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%